2021
DOI: 10.35530/it.072.01.1784
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of CO2 emission and economic factors on infants health: a case study for Pakistan

Abstract: This study has attempted to investigate the consequences of CO2 emissions on infants’ health in Pakistan over the period of 1975 to 2013. Several economic factors have been employed in our analysis and the estimates show insignificant impact of CO2 emissions in affecting children mortality. Increasing health facilities lowers children mortality over a short period were also observed but the relationship inversed in the long-run. In short-run, urbanization appeared as a decreasing factor to children mortality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…In this way, they enjoy an expectedly long and healthy life. The result is consistent withthe literature which shows that the public spending on healthcare leads to low child mortality rates [31].The per capita income and growth affect the infant mortalityvery significantly [41].The study results are also consistent with [46], which strengthens their validity. In the case of spending, although showingsigns positively, the statistics are insignificant in this study, which might be explained by the percentage of the amount being spent on health, which might not have significant enough impact to be noticeable.…”
Section: Summary Statisticssupporting
confidence: 91%
See 3 more Smart Citations
“…In this way, they enjoy an expectedly long and healthy life. The result is consistent withthe literature which shows that the public spending on healthcare leads to low child mortality rates [31].The per capita income and growth affect the infant mortalityvery significantly [41].The study results are also consistent with [46], which strengthens their validity. In the case of spending, although showingsigns positively, the statistics are insignificant in this study, which might be explained by the percentage of the amount being spent on health, which might not have significant enough impact to be noticeable.…”
Section: Summary Statisticssupporting
confidence: 91%
“…Moreover, [25], have used panel data analysis and discovered a negative effect of public health expenditures. The authors of [41] revealed that an increase in public spending improves child mortality. A negative relationship was also found between health expenditures and infant mortality rate [42,43].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the comprehensive study of the debate between structuralists and monetarists, and following the trend of inflation and growth in Pakistan, we expect that the growth-inflation relationship is negative in the case of Pakistan, supporting the monetarists' view. Naeem et al (2021) argued that Pakistan is a developing economy where there are no strict environmental policies implemented for the benefit of enhancing economic growth. We are also hopeful to find a long-run relationship between these variables.…”
Section: Introductionmentioning
confidence: 99%